2021
DOI: 10.1021/acsami.1c15271
|View full text |Cite
|
Sign up to set email alerts
|

Interface-Stabilized Layered Lithium Ni-Rich Oxide Cathode via Surface Functionalization with Titanium Silicate

Abstract: Nickel-rich lithium metal oxide cathode materials have recently be en highlighted as next-generation cathodes for lithium-ion batteries. Nevertheless, their relatively high surface reactivity must be controlled, as fading of the cycling retention occurs rapidly in the cells. This paper proposes functionalized nickel-rich lithium metal oxide cathode materials by a multipurpose nanosized inorganic materialtitanium silicon oxidevia a simple thermal treatment process. We examined the topologies of the nano-titan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 83 publications
0
7
0
Order By: Relevance
“…The cycled P-LN83 cathode showed a relative ratio of 31.00% for Li x PO y F z while the recovered 0.5 POS-LN83 and 1.0 POS-LN83 cathodes only showed relative ratios of 16.93% and 18.63%, resepctively. In addition, the F 1s spectra of the recovered 0.5 POS-LN83 and 1.0 POS-LN83 cathodes contained an intrinsic peak at 687.1 eV, which could be assigned to a Si−F functional group 68,69 that was probably formed by a F − scavenging reaction. Considering the LiF and Si−F functional groups in the artificial CEI layers, the overall F 1s relative ratio was lower for the recovered 0.5 POS-LN83 and 1.0 POS-LN83 cathodes than for the cycled P-LN83 cathode, because the recovered P-LN83 cathode still showed a higher ratio for Li x PO y F z , a decomposition product.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cycled P-LN83 cathode showed a relative ratio of 31.00% for Li x PO y F z while the recovered 0.5 POS-LN83 and 1.0 POS-LN83 cathodes only showed relative ratios of 16.93% and 18.63%, resepctively. In addition, the F 1s spectra of the recovered 0.5 POS-LN83 and 1.0 POS-LN83 cathodes contained an intrinsic peak at 687.1 eV, which could be assigned to a Si−F functional group 68,69 that was probably formed by a F − scavenging reaction. Considering the LiF and Si−F functional groups in the artificial CEI layers, the overall F 1s relative ratio was lower for the recovered 0.5 POS-LN83 and 1.0 POS-LN83 cathodes than for the cycled P-LN83 cathode, because the recovered P-LN83 cathode still showed a higher ratio for Li x PO y F z , a decomposition product.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The cycled P-LN83 cathode showed a relative ratio of 31.00% for Li x PO y F z while the recovered 0.5 POS-LN83 and 1.0 POS-LN83 cathodes only showed relative ratios of 16.93% and 18.63%, resepctively. In addition, the F 1s spectra of the recovered 0.5 POS-LN83 and 1.0 POS-LN83 cathodes contained an intrinsic peak at 687.1 eV, which could be assigned to a Si−F functional group 68,69 that was probably formed by a F − scavenging reaction.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Among these efforts, researchers have shown that surface coating remains as an effective and facile route. They have developed different inorganic and polymeric coatings via wet chemistry vapor-phase processes showing superior performance on NMC811 [30][31][32]. In the past decade, atomic layer deposition (ALD) has emerged as a unique vapor-phase technique enabling high-quality conformal and uniform films over either electrode powders or prefabricated electrodes [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…With the demand for electric vehicles, electronic devices, and large energy storage equipment, the development of low-cost and high-energy-density secondary energy-storage equipment such as lithium-ion batteries (LIBs) has become particularly important. As one of the critical components in LIBs, the cathode materials directly affect the energy density, safety performance, and cycle lifespan . The energy density of LiNi x Co y Mn 1– x – y O 2 (NCM, with x ≥ 0.6) is higher than 300 W h kg –1 , far higher than other traditional cathode materials such as LiFePO 4 , LiMn 2 O 4 , and LiCoO 2 , and these nickel-based layered oxides, which are widely considered to be the most promising cathode material for the next generation of LIBs, have the advantages of low raw material cost and low toxicity. Currently, some effective strategies to enhance the energy density of nickel-based cathodes are direct broadening of the voltage window and increasing the nickel proportion. However, some critical issues especially voltage and capacity decaying under a high voltage window limit the development of the nickel-rich cathode, and these problems may be caused by the following reasons: (1) Ni 4+ cation migration and multiphase transition with nickel contents increasing; (2) oxygen release during·a reaction; (3) insufficient utilization of lithium ions; and (4) inter/intragranular cracking and fragmentation. , …”
Section: Introductionmentioning
confidence: 99%